Urothelial carcinoma of urinary bladder with histologic grading: a study in a tertiary care hospital, Bangladesh - Islam, M. Ariful; Mir, Ratim; Jinnah, Mohammed S. Ali; Sweety, Rumana A.; M. M. Rahman (International Journal of Research in Medical Sciences, 2023)
Background: Urinary bladder cancer is one of the most common forms of all cancers in the world. It is the ninth leading cause of death from cancer among men. The incidence of urinary bladder cancer in Bangladesh is increasing day by day. The aim of the study was to evaluate different clinic-pathological parameters of urothelial carcinoma of urinary bladder with the grade of the tumor. Methods: This study was a cross sectional study done over a period of two years, from March 2018 to February 2020 at the department of pathology, Dhaka medical college, Dhaka. Total 73 samples were collected, fixed overnight in 10% buffered formalin and stained with hematoxylin and eosin staining. Pathological grading was confirmed and different clinic-pathological parameters were evaluated. Results: Most of the cases (22 cases, 30.1%) were found in the fifth decade (51-60). Mean age of the patients was found to be 60.85 (±12.72) years, 58 (79.5%) cases were male and 15 (20.5%) cases were female with male to female ratio of 3.9:1. Most of the cases (49 cases, 67.1%) were smokers. Most common clinical presentation was hematuria (91.8% cases), most frequent tumor location was the lateral wall of the urinary bladder and 75.3% cases were reported as high-grade urothelial carcinoma. Conclusions: Different clinic-pathological parameters with histologic grading were evaluated in this study which may have a significant impact in epidemiology, diagnosis and assessment of biological behavior of urothelial carcinoma.